Paradigm Shift in Urban Mobility Towards Factor 10 of Automobility - Janasz, Tomasz (Advances in Information Systems and Business Engineering,, 2018)
Tomasz Janasz demonstrates that digital technologies and new mobility concepts can lead to a reduction of the automobiles in urban areas by a factor of 10. The book features two vivid case studies of such digital mobility concepts: TwoGo by SAP and smexx. The author proposes six prototypes of business models for 'Shared Automobility Services'. Janasz offers also the 'Transformative Literacy' for designing sustainable urban mobility systems of the future. The author elaborates on the socio-political patterns of urban mobility by presenting the case of the City of Basel (Switzerland). He proposes the framework of 'Integrated Sustainable Urban Mobility' to explain how to overcome car dependence in cities. Contents New Mobility Concepts Autonomous Vehicles Digital Technologies Business Models Policy Interventions for Sustainable Mobility Target Groups Researchers in the fields of innovation management, sustainability, and future urban transportation systems Practitioners in the fields of urban mobility, automotive industry, digital technologies, and business model design The Author Dr. Tomasz Janasz is a business consultant for digital innovation and transformation at a German multinational software corporation. His focus lies on digital business models for the Internet of Things with the main interest in designing efficient urban mobility systems. Series Editors The book series Advances in Information Systems and Business Engineering is edited by Prof. Dr. Ulrike Baumöl, Prof. Dr. Jan vom Brocke and Prof. Dr. Reinhard Jung.